Exploring the benefits of creativity in education, media, and the arts - Silton, Nava R. (A volume in the advances in media, entertainment, and the arts (AMEA) book series, 2017)
This book is a pivotal reference source for the latest scholarly research on the stimulation and implementation of creative thinking in academic and professional environments, highlighting the foundations of creativity from theoretical and neuroscientific perspectives.